2012
DOI: 10.3109/0886022x.2012.672266
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resistive Index by Color Doppler Imaging of Orbital Arteries in Type II Diabetes Mellitus Patients with Microalbuminuria

Abstract: Our study indicates that RI might be a useful marker for early diagnosis and follow-up of diabetic retinopathy, and orbital RI assessment would be beneficial for diabetic patients with retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 17 publications
2
24
1
1
Order By: Relevance
“…have also showed increased RI values of the orbital arteries in diabetic retinopathy patients than patients without retinopathy. [6] In our study, all orbital RI values of patients with hypertensive retinopathy were found to be similar compared to patients without retinopathy.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…have also showed increased RI values of the orbital arteries in diabetic retinopathy patients than patients without retinopathy. [6] In our study, all orbital RI values of patients with hypertensive retinopathy were found to be similar compared to patients without retinopathy.…”
Section: Discussionsupporting
confidence: 64%
“…Circulatory parameters in the retrobulbar blood vessels are one of them. [34567] Hypertension alters vascular resistance in eyes, and is a major risk factor for arteriosclerosis, and advanced arteriosclerosis occurs with increasing age which indicates long duration of hypertension. Previously, a little number of studies in literature has been performed to evaluate the RIs of orbital arteries in patients with hypertension.…”
mentioning
confidence: 99%
“…After excluding studies one by one, the variation ranges for heterogeneity were as follows: 77% to 87% for central retinal artery PSV, 76% to 96% for short posterior ciliary artery PSV, 45% to 78% for ophthalmic artery RI, and 93% to 96% for central retinal artery RI in group 1; 75% to 83% for ophthalmic artery EDV, 76% to 86% for central retinal artery EDV, 72% to 87% for ophthalmic artery RI, 89% to 96% for central retinal artery RI, and 52% to 91% for short posterior ciliary artery RI in group 2; and 65% to 88% for ophthalmic artery RI in group 3. No significant changes were found in the above comparisons, except that after the study by Basturk's et al 10 was excluded for the short posterior ciliary artery RI in group 1, the heterogeneity disappeared ( I 2 = 0%; P heterogeneity = .45).…”
Section: Resultsmentioning
confidence: 75%
“…Another two trials assessed the diagnosis of DRP. Whereas Arai et al [12] examined the diagnosis of DRP among patients suffering from non-insulin-dependent diabetes, Basturk and colleagues [13] investigated the diagnosis of DRP in patients suffering from diabetes type II with microalbuminuria. Prediction of glaucoma progression was investigated in three studies two using the Humphrey field analyser and one the Heidelberg retina tomography as the reference test [1416].…”
Section: Resultsmentioning
confidence: 99%
“…Of the two studies assessing ICS, one used peak flow velocity [10] and one the RI [11]. Both studies examining the diagnostic value of CDI in DRP used RI as investigational parameter [12, 13]. Two studies assessing ischemia and neovascularization after CRVO, used the parameter “minimum velocity” [6, 19].…”
Section: Resultsmentioning
confidence: 99%